The epidemic of acute lymphoid leukemia in China: current trends and future prediction - Zhu, Wenxuan; Liu, Shixuan; Shi, Ying; Tang, Qingyu; Sun, Jianzhong; Bai, Ruhai; Sun, Zhonghe; Du, Zhaoqing (Frontiers in Oncology, 2023)
Background China has experienced one of the fastest increases in the incidence of acute lymphoid leukemia (ALL). The aim of this study was to assess the long-term trends of the incidence and mortality of ALL in mainland China between 1990 and 2019 and to project these trends through 2028. Methods Data on ALL were extracted from the Global Burden of Disease Study 2019; population data were extracted from World Population Prospects 2019. An age-period-cohort framework was used in the analysis. Results The net drift for the incidence of ALL was 7.5% (95% confidence interval [CI]: 7.1%, 7.8%) per year in women and 7.1% (95% CI: 6.7%, 7.6%) in men, and local drift was found to be higher than 0 in every studied age group (P<0.05). The net drift for mortality was 1.2% (95% CI: 1.0%, 1.5%) in women and 2.0% (95% CI: 1.7%, 2.3%) in men. Local drift was lower than 0 in boys aged 0-4 years and girls aged 0-9 years and higher than 0 in men aged 10-84 years and women aged 15-84 years. The estimated period relative risks (RRs) for both incidence and mortality showed increasing trends in the recent period. The cohort RRs for incidence showed increasing trends in both sexes; however, the cohort RR for mortality was decreased in the recent birth cohort (women born after 1988-1992 and men born after 2003-2007). Compared with that in 2019, the incidence of ALL in 2028 is projected to increase by 64% in men and 75% in women, and the mortality is predicted to decrease by 11% in men and 14% in women. The proportion of elderly individuals with incident ALL and ALL-related death was projected to increase. Conclusions Over the last three decades, the incidence and mortality rates of ALL have generally increased. It is projected that the incidence rate of ALL in mainland China will continue to increase in the future, but the associated mortality rate will decline. The proportion of elderly individuals with incident ALL and ALL-related death was projected to increase gradually among both sexes. More efforts are needed, especially for elderly individuals.